State ownership and corporate investment: evidence from Vietnamese stock market - Tran, Quoc Trung; Nguyen, Xuan Minh; Nguyen, Tuan Duong; Nguyen, Thi Trung; Dao, Thi Huong; Nguyen, Quang Tam (Journal of International Economics and Management, 2023)
The literature shows that the relationship between state ownership and corporate investment is debatable. This study examines this relationship in Vietnam as a transitional economy. Our sample consists of 4,680 observations from 2009 to 2020. Using fixed effects and random effects for panel data, random effects Tobit, and pooled OLS, we find that state ownership decreases investment expenditures. Moreover, this negative impact is stronger if the firms are financially unconstrained. Our results indicate that weak corporate governance and soft budget constraints arising from state ownership may fail to determine investment decisions. A government’s negative attitude toward risk and conservatism may effectively affect corporate investment.